Modern Chinese poetry : theory and practice since 1917 - Yeh, Michelle, 1955- (Yale University Press, 1991)
Modern Chinese poetry, says Michelle Yeh, is both a revolt against an ancient literary tradition that has lost its vitality and a response to the swiftly changing sociopolitical and cultural conditions of the twentieth century. In this new book-the first full-length critical study devoted to the subject-Yeh examines the theoretical and artistic aspects of the poetry as well as its historical and literary contexts. She explains why modern Chinese poetry has evolved the way it has and compares it with the three-thousand-year Chinese classical tradition. Among factors contributing to the revolution in poetry, Yeh discusses the loss of a universal value system and a clearly defined role for the art. With the decline also of a sympathetic audience, there was created a private, introverted, and idiosyncratic world in which artistic experiment occurs in ways that would have been inconceivable in traditional poetics. Yeh focuses on some stylistic features unique to modern Chinese poetry, examining in particular the poetic of discontinuity and the circular form. And she discusses ways in which Chinese poetry since 1917 has become receptive to the influence of modernism in the West and has both integrated and transformed tradition. With her insight into the obstacles that face modern Chinese poets, Yeh provides an analysis whose implications transcend the purely literary realm and are relevant to the social and political life of modern China. The book contains many original translations of poems that either have never been translated before or have not been translated well. An appendix provides the Chinese original for all the poems discussed. The book also includes a glossary of Chinese names shown in Chinese characters, in Pinyin romanization, and in Wade-Giles romanization.